EFFECT OF TRYPANOSOMA EVANSI INFECTION ON TRACE ELEMENTS METABOLISM IN RABBITS. - A. Kadir, M.; Abdul Majeid, L.; E. Ahmed, M. (The Iraqi Journal of Veterinary Medicine, 1990)
This study was carried out to show the effect of Trypanosoma evansi on trace elements metabolism in local breed rabbits fed on either milk or standard diets. the dose of Trypanosoma evansi infection was 2x10 per rabbit. It found that Trypanosoma infection lead to increase in the concentration of copper in both serum and liver, but it lead to decrease the iron serum concentra- tion. The effect of infection on serum copper was greater in rabbits fed milk diets. On the other hand, it has been found that the infection caused an increase in serum iron in those rabbits fed on standard diet. Although, effect on plasma concentration in Trypanosoma infection had no significant zinc, it lead to increase liver zinc rabbits fed on either dietary treatments. Its effect was greater in those fed on milk diet.